Engineering education standards - Stefanova, Tereza (Yearbook Telecommunications, 2022)
Professions such as engineering, architecture, medicine and others are related to work that directly affects the life of society. The engineering profession is rapidly changing and extremely responsible, and requires rigorous assessment of the competence and commitment of engineering professionals. Therefore, various associations, organizations, authorized agencies of institutions of higher education, etc. set and maintain standards that are internationally recognized and relevant to the industry. The article examines organizations related to accreditation and quality assurance in engineering education in Europe and beyond, and highlights the most important features of the EUR-ACE system. The article shows data on engineering programs with the EUR-ACE label in some EU countries and Bulgaria. A brief description of the knowledge, competencies, skills and abilities that bachelor’s and master’s degree graduates should possess in their engineering field is provided.